Do Non Alcoholic Fatty Liver Disease Patients Have more Severe Metabolic Syndrome - Abdul Basit, Muhammad Ali, Muazma Batool, Hafiz Abdul Salam Jakhrani, Atiya Aamer, Maryam Naz (Pakistan Journal of Medical & Health Sciences, 2022)
Background and goal: Alcohol-unrelated fatty liver disease (NAFLD) is a frequent type of chronic liver disease (CLD) that is rapidly spreading around the world. The study’s primary goal is to evaluate the severity of metabolic syndrome in people with nonalcoholic fatty liver disease. Materials and methods: From January to July 2019, Shalimar Medical and Dental College in Lahore, Pakistan, conducted this cross-sectional study. Through the use of non-probability sampling, the data was gathered. 100 patients with hepatic cirrhosis provided the data. The participants in this study ranged in age from 20 to 60. For the serum examination of liver enzymes, blood was drawn. Results: A correlation between the severity of the metabolic syndrome and NAFLD was found in this study, which included data from 100 individuals with biopsy-proven NAFLD. The patients were 45.67 3.56 years old on average. Compared to the normal control (11,3.42), the ALT levels in the patients were 258.291.73, 79.6628.63, and 50.73 8.4 correspondingly. Patients with cirrhosis, alcoholic liver disease, and viral hepatitis all had considerably higher aspartate aminotransferase levels. The significant frequency elevated aminotransferases and of NAFLD in IR-obese adolescents, as well as the potential consequences for their health, are concluded. The strong connections between NAFLD and MetS encourage the screening for additional MetS co-morbidities.